Prescription for nutritional healing - Balch, James F. (: AVERY PUBLISHING GROUP INC., 1990)
Elements of health. The desroders. Remedies and therapies. Ascorbic acid flush. Blood purifier. Improving brain function. Chelation therapy. Colon cleansing
Keywords: ALERGIAS; ANOREXIA NERVIOSA; MINERALES; VITAMINA B